The Implementation of the Merdeka Curriculum in Arabic Language Instruction at SMPIT Shohibul Muslimin Serang - Kurniawan, Ahmad; Faedurrohman; Iffan Permana, Muhammad; Azizi Syukrillah, Muhammad; Yusril Ramadhan, Muhammad; Halim, Wildan; Hasan, Firdah (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2024)
This study analyzes the implementation of the Merdeka Belajar Curriculum in Arabic language learning at SMPIT Shohibul Muslimin Serang. The Merdeka Belajar Curriculum is an educational approach that emphasizes student learning independence, curriculum flexibility, and the use of technology. The purpose of this study was to determine the application, implementation strategies, and challenges of the Merdeka Belajar Curriculum in the context of Arabic language learning at SMPIT Shohibul Muslimin Serang and to evaluate its impact on Arabic language learning achievement. This research method was a case study with a qualitative approach. Data were collected through classroom observations, interviews with respondents, and analysis of curriculum-related documents. The results showed that the Merdeka Belajar Curriculum implementation strategy at SMPIT Shohibul Muslimin Serang involved a shift in learning paradigms to become more student-centered. Teachers act as facilitators and students have more control over their learning process. This implementation further supports student learning independence. However, several obstacles were also identified, including students’ difficulties in learning interest and challenges in measuring learning achievement in a broader and contextual manner. Nevertheless, the implementation of the Merdeka Belajar Curriculum has had a positive impact on student motivation and engagement in Arabic language learning